2018
DOI: 10.1049/iet-cvi.2017.0468
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐dimensional long short‐term memory networks for artificial Arabic text recognition in news video

Abstract: This study presents a novel approach for Arabic video text recognition based on recurrent neural networks. In fact, embedded texts in videos represent a rich source of information for indexing and automatically annotating multimedia documents. However, video text recognition is a non-trivial task due to many challenges like the variability of text patterns and the complexity of backgrounds. In the case of Arabic, the presence of diacritic marks, the cursive nature of the script and the non-uniform intra/inter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…It is however important to recall that UPTI contains synthetically generated text lines and do not offer the same kind of recognition challenges as those encountered in case of scanned documents or video text. In case of video text, Zayene et al [114] reported 96.85% recognition rate of on a relatively smaller set of around 8000 Arabic text lines. For Urdu caption text, Tayyab et al [134] reports 93% recognition rate on approximately 20,000 text lines.…”
Section: Text Recognition Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is however important to recall that UPTI contains synthetically generated text lines and do not offer the same kind of recognition challenges as those encountered in case of scanned documents or video text. In case of video text, Zayene et al [114] reported 96.85% recognition rate of on a relatively smaller set of around 8000 Arabic text lines. For Urdu caption text, Tayyab et al [134] reports 93% recognition rate on approximately 20,000 text lines.…”
Section: Text Recognition Resultsmentioning
confidence: 99%
“…In the context of cursive text, a holistic technique based on multi-dimensional LSTMs is presented in [114] for recognition of Arabic video text. The technique is evaluated on two datasets ACTiV [115] and the ALIF [116,117] and reports high recognition rates.…”
Section: Text Recognitionmentioning
confidence: 99%
“…In recent years, several novel works for cursive text detection and recognition in video images have been developed [51]- [54], while a limited work is presented for cursive text recognition in natural scenes [55]- [57]. Ahmed et al [55], modified the maximally stable extremal region method to extract the scale-invariant features and passed to the multi-dimensional long short term memory (MDLSTM) classifier.…”
Section: B Cursive Text Recognition In Video and Natural Scene Imagesmentioning
confidence: 99%
“…These results have been compared with Sakhr, ABBYY, and NovoDynamics, which are known commercial Arabic OCR systems, and the results were promising. Zayene et al (2018b) presented an Arabic video embedded text recognition system based on deep learning approach, they used MDLSTM network as input layers, so the MDLSTM learn the features from the raw input image, for the output layer they use the CTC with softmax activation function. The suggested method has been trained and evaluated using the AcTiV-R database which is part of AcTiv dataset consists of 10,415 text-lines images, 44,583 words.…”
Section: Arabic Text Recognition With Deep Learningmentioning
confidence: 99%